Combining nanoparticle albumin-bound paclitaxel with camrelizumab in advanced soft tissue sarcoma: activity, safety, and future perspectives - Zhichao Tian; Yushen Feng; Yang Yang; Xu Liu; Guoxin Qu; Yonghao Yang; Xin Wang; Jiaqiang Wang; Peng Zhang; Weitao Yao (Frontiers Media S.A., 2024)
Background: It is still uncertain whether Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) and programmed cell death protein 1 (PD-1) inhibitor have synergistic effects on metastatic soft tissue sarcomas (STSs). The purpose of this study was to evaluate the safety and activity of nab-paclitaxel plus camrelizumab (a PD-1 inhibitor) in patients with advanced STS who had previously failed chemotherapy.Methods: In this single-center, open-label, single-arm phase II clinical trial, patients with advanced (unresectable or metastatic) STS who had previously failed chemotherapy received up to six cycles of nab-paclitaxel plus camrelizumab, whereas camrelizumab treatment was continued for up to 1 year. The median progression-free survival (PFS), objective response rate (ORR) and safety were collected and evaluated.Results: This trial included 40 patients (28 men and 12 women). The overall ORR was 22.5%, and the median PFS was 1.65 months (95% confidence interval [CI], 1.3-2.0 months). Patients with epithelioid sarcoma demonstrated a longer PFS compared with those with other histological subtypes (2.3 months vs. 1.5 months, respectively); however, this difference was not significant. Patients who had received only one line of previous chemotherapy had a significantly longer PFS compared with those who had undergone two or more lines of previous chemotherapy (2.8 months vs. 1.3 months, respectively, p = 0.046). In terms of safety, the toxicity of this combination therapy is mild and no serious adverse events have occurred.Conclusion: Nab-paclitaxel plus camrelizumab exhibited modest activity and mild toxicity in treating epithelioid sarcoma, angiosarcoma, and fibrosarcoma. The overall effectiveness of this treatment regimen for advanced STS is relatively low. Further research on combining nab-paclitaxel with effective drugs, including chemotherapy and targeted agents, for these specific STS subtypes is needed.